ENHANCING NEONATAL HYPERBILIRUBINEMIA MANAGEMENT: A COMMUNITY SERVICE PROGRAM AT RSUD AJI BATARA DEWA SAKTI - Sampurna, Mahendra Tri Arif; Niko Azhari , Hidayat; Husnina, Zida; Widodo, Muhammad Rizky; Azhari, Syah Reza Budi (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This study  details an intervention through a community service conducted at the Regional General Hospital Aji Batara Agung Dewa Sakti, focusing on the improvement of healthcare professional’s skills in managing neonatal hyperbilirubinemia. The program conducted in two days, including a one-day socialization and one-day training session. Comprehensive approach was used with a special emphasis on the BiliNorm application. The intervention result shows higher score in post test compared to pre-test, indicating significant improvements (P<0.001) in participant’s knowledge and skills. Statistical analysis highlighted the effectiveness of the training program in demonstrating a successful transfer of knowledge on the usage of BiliNorm application, AirBiliSun and AirBiliNest. This study highlighted the positive impact of this program on early detection and management practices.